Agricultura familiar na mesorregião Oeste do Paraná: cooperativismo como forma de integração para a sustentabilidade dos estabelecimentos familiares - Rahmeier, Daliane (2016)
The main objective of this thesis was to analyze the characteristics of family agriculture in the western mesoregion of Paraná, evidencing the municipalities that present low IDH indicators and poverty rate. For this, the historical, economic and institutional trajectory of family agriculture was evaluated, contextualizing the importance of cooperativism as a form of integration for the sustainability of these establishments. In this sense, the aim was to characterize the classic and contemporary bases of family agriculture, the historical context and the occupation of the area of the Western Paranaense Meso-region, the configuration of the family agricultural sector and the role of the cooperativism of the mesoregion, as well as to analyze the municipalities that presented The lowest indicators of IDH and poverty rate, verifying the process of selecting the integration system with family agriculture. The western mesoregion of Paraná has in its socioeconomic context a considerable representation of the agricultural sector and more specifically of family agriculture, which is present throughout the mesoregion. Methodologically, secondary and primary data were used, which potentiated the verification of the reality experienced by family farmers in the regions that present poverty indicators and pointed out the reality of the agricultural establishments that make up the universe of the studied area. Studies have shown that cooperativism and its forms of integration in the western mesoregion of Paraná have a strong relationship with regional development and the relationships between family agriculture. The results showed that in this area of development of rural properties, there is a niche of poverty located in the family settlements of the western mesoregion, contrasting with the richness of the development of the West of Paraná. These properties are located in Diamante d'Oeste , Diamante do Sul and Ramilândia, which compared to the averages presented by the western mesoregion, the income of family establishments located in the identified municipalities is relatively smaller and, in this sense, the concern of the survival of these Family establishments because of the lower performance in relation to the average presented by the mesoregion. It was clear that this format excludes part of the family farmers from the production process, given the installation cost required by the integrators and that are the responsibility of the producer.